Integrin, Exosome and Kidney Disease - Shen, An-Ran; Zhong, Xin; Tang, Tao-Tao; Wang, Cui; Jing, Jing; Liu, Bi-Cheng; Lv, Lin-Li (Frontiers in Physiology, 2021)
Integrins are transmembrane receptors that function as noncovalent heterodimers that mediate cellular adhesion and migration, cell to cell communication and intracellular signaling activation. In kidney, latency associated peptide-transforming growth factor β (TGF-β) and soluble urokinase plasminogen activator receptor (suPAR) were found as the novel ligands of integrins that contribute to renal interstitial fibrosis and focal segmental glomerular sclerosis (FSGS). Interestingly, recent studies revealed that integrins are the compositional cargo of exosomes. Increasing evidence suggested that exosomal integrin played critical roles in diverse diseases such as tumor metastasis, neurological disorders, immunology regulation and other processes. This review will focus on the biology and function of exosomal integrin, emphasizing its potential role in kidney disease as well as its implications in developing novel therapeutic and diagnosis approaches for kidney disease.